2022
DOI: 10.1111/bcp.15607
|View full text |Cite
|
Sign up to set email alerts
|

A critical appraisal of controlled studies investigating malformation risks following pregabalin use in early pregnancy

Abstract: In March 2022, the Summary of Product Characteristics for the Lyrica brand of pregabalin was updated with warnings regarding malformation risks. This literature review and critical appraisal aims to explore whether these Summary of Product Characteristics updates are justified and provide clarity on the risk–benefit balance for pregabalin use in early pregnancy. A literature review was conducted in May 2022 to identify English language comparative studies of any design providing data about first trimester mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Pregabalin is a new-generation antiepileptic that reduces multiple stimulus output by reducing depolarization-induced calcium flux (16). It is indicated for the treatment of epilepsy, peripheral neuropathic pain, fibromyalgia, postherpetic neuralgia, chronic pruritus, restless legs syndrome, generalized anxiety disorder and insomnia (17,18). Unfortunately, there is considerable evidence in the literature of pregabalin abuse (17,19,20), and studies have shown that pregabalin abuse can lead to addiction (20), poisoning (19), and drug withdrawal syndromes (17).…”
Section: Introductionmentioning
confidence: 99%
“…Pregabalin is a new-generation antiepileptic that reduces multiple stimulus output by reducing depolarization-induced calcium flux (16). It is indicated for the treatment of epilepsy, peripheral neuropathic pain, fibromyalgia, postherpetic neuralgia, chronic pruritus, restless legs syndrome, generalized anxiety disorder and insomnia (17,18). Unfortunately, there is considerable evidence in the literature of pregabalin abuse (17,19,20), and studies have shown that pregabalin abuse can lead to addiction (20), poisoning (19), and drug withdrawal syndromes (17).…”
Section: Introductionmentioning
confidence: 99%
“…It is indicated for use in epilepsy, peripheral neuropathic pain, fibromyalgia, generalized anxiety disorder, and post-herpetic neuralgia (2). Pregabalin is also used to treat chronic itching, restless legs syndrome, social anxiety disorder, insomnia, and bipolar disorder (3). Unfortunately, however, much evidence exists in the literature about pregabalin abuse (2,4,5).…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to certain methodological flaws in the study and low-quality evidence that suggested the possibility of only a minor, unconfirmed risk that could not be solely associated with foetal exposure to pregabalin. 5 A multi-centred study should be conducted to develop a better understanding of the role of pregabalin in causing congenital malformations. However, since the MHRAreviewed Nordic study is the largest population-based study currently available, guidelines given out by the MHRA and DRAP regarding patient exposure to pregabalin during pregnancy cannot be ignored.…”
mentioning
confidence: 99%